PENYALAHGUNAAN INSTRUMEN KEPAILITAN ATAU PKPU OLEH DEBITOR SETELAH MEMPEROLEH FASILITAS KREDIT DARI LEMBAGA KEUANGAN - Prajogo, Timotius William (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The 5C principles are important for creditors to give loan to debtors. However, nowadays especially collateral cannot be the guarantee for debtor’s debt if the debtor is breaching the contract, because many of the financial institutions are dare to take a risk by giving higher loan than its collateral’s worth. This condition can bring a risk if there were bankruptcy happened to debtor; therefore, it is not rare that there is clause in loan agreement to protect creditors, by not allowing debtor voluntary asked self-bankruptcy petition, although this kind of clause is contradicts with the nature of bankruptcy law. The concept in Law number 37 years 2004, categorize as simple to be granted by commercial court. Unfortunately, the bankruptcy’s instrument often misused by parties who have bad faith and also for the suspension of payment. Moreover, the creditors will get impact from the parties that have a bad faith. As the legal protection, it can do some legal efforts such: suspension of debt’s payment, lawsuit, cassation, judicial review and criminal indictment.